Theoretical Review of Pay Restructuring in Uganda's Public Service Health Sector. - Olum, Samson; Adyanga, Francis Akena; Ocan, Johnson (Kabale University, 2024)
This article examines the impact of wage reforms on service delivery, financial stability, managerial efficiency, and donor influence and focuses on the public health sector in Uganda. Like other reforming countries, Uganda also implemented salary structure reform for various reasons, but the most important ones were to pay civil servants a living wage, make remuneration transparent, align the salary structure with the single-spine structure, and consequently increase the number of employees' motivation and efficiency in service delivery. The study analyzed research articles, policy documents, reports, and media coverage on pay changes for public health workers. Key findings show that the original goal of wage reforms, such as the single-spine structure has not been achieved; several pay scale structures were reintroduced. Different service models are used to calculate wages. Similar cadres of civil servants receive different salary grades; and wage allocation receives more funding than other areas, such as development and supplies. The results suggest that salary increases affect allocations in other important areas but do not always result in public health workers' commitment to service. Compromise and negotiation have played an important role in public sector wage restructuring. A review of wage reforms implemented across Uganda's public sector will be based on the recommendations and issues addressed in this study. The study provides crucial benchmarks with regard to wage reform strategies that promote diversity in the public sector and the distribution of authorities. This study is unique because it focuses on wage restructuring in the public sector to align practices with policies. Although based on a review of relevant documents, it was conducted for the first time in Uganda.